DUSTiER (DUST in the Epoch of Reionization): dusty galaxies in cosmological radiation-hydrodynamical simulations of the Epoch of Reionization with RAMSES-CUDATON - Lewis, Joseph; Ocvirk, Pierre; Dubois, Yohan; Aubert, Dominique; Chardin, Jonathan; Gillet, Nicolas; Thélie, Émilie (Arxiv, 2023)
In recent years, interstellar dust has become a crucial topic in the study of the high redshift Universe. Evidence points to the existence of large dust masses in massive star forming galaxies already during the Epoch of Reionization, potentially affecting the escape of ionising photons into the intergalactic medium. Moreover, correctly estimating dust extinction at UV wavelengths is essential for precise ultra-violet luminosity function (UVLF) prediction and interpretation. In this paper, we investigate the impact of dust on the observed properties of high redshift galaxies, and cosmic reionization. ...